Managing ecosystems in a sea of uncertainty: invasive species management and assisted colonizations. Issue 4 (26th March 2021) - Rendall, Anthony R.; Sutherland, Duncan R.; Baker, Christopher M.; Raymond, Ben; Cooke, Raylene; White, John G.
Abstract: Managing ecosystems in the face of complex species interactions, and the associated uncertainty, presents a considerable ecological challenge. Altering those interactions via actions such as invasive species management or conservation translocations can result in unintended consequences, supporting the need to be able to make more informed decisions in the face of this uncertainty. We demonstrate the utility of ecosystem models to reduce uncertainty and inform future ecosystem management. We use Phillip Island, Australia, as a case study to investigate the impacts of two invasive species management options and consider whether a critically endangered mammal is likely to establish a population in the presence of invasive species. Qualitative models are used to determine the effects of apex predator removal (feral cats) and invasive prey removal (rabbits, rats, and mice). We extend this approach using Ensemble Ecosystem Models to consider how suppression, rather than eradication influences the species community; and consider whether an introduction of the critically endangered eastern barred bandicoot is likely to be successful in the presence of invasive species. Our analysis revealed the potential for unintended outcomes associated with feral cat control operations, with rats and rabbits expected to increase in abundance. A strategy based on managing prey species appeared to have the most ecosystem‐wide benefits, with rodent control showing more favorable responses than a rabbit control strategy. Eastern barred bandicoots were predicted to persist under all feral cat control levels (including no control). Managing ecosystems is a complex and imprecise process. However, qualitative modeling and ensemble ecosystem modeling address uncertainty and are capable of improving and optimizing management practices. Our analysis shows that the best conservation outcomes may not always be associated with the top‐down control of apex predators, and land managers should think more broadly in relation to managing bottom‐up processes as well. Challenges faced in continuing to conserve biodiversity mean new, bolder, conservation actions are needed. We suggest that endangered species are capable of surviving in the presence of feral cats, potentially opening the door for more conservation translocations.